Governança corporativa e desempenho financeiro das cooperativas da Cresol/PR - Cagnini, Wilmar (2019)
The cooperatives’ participation in the Brazilian credit market has increased considerably in recent years. Moreover, these institutions are responsible for circulation of 2.97% of the total national financial fullness, reaching more than 92.25 Billion Real until December 2017. The South region is where these cooperatives have the main participation. Interested in this market, the Central Bank of Brazil published in 2009 the Guide to Guidelines for Good Governance Practices, directed to Credit Cooperatives, being that its adoption aims at the interests’ alignment with the purpose of optimizing and maximizing the economic value of these organizations, through the facilitation of access to resources and improvements in gestational quality, providing longevity to this sector. Knowing this context, the adoption of the corporate governace’s practice and its purposes, the main goal is to analyze if the observance of the corporate governance practices, in their different levels of maturity, could justify or create synergy able to influence in the financial performance of rural credit cooperatives linked to the Cresol system, located in the Paraná state. The theoretical framework of this work is based on the theory of the agency, of related costs and the asymmetry of information and the conflicts of the Agency in the credit cooperatives. The relationship between the different stakeholders served as the basis for the constructs between financial indicators and corporate governance indicators, based on the corporate governance´s principles issued by BACEN, OCB, IBGC and WCCU. This research is classified as empirical analytical of descriptive character, regarding the objectives, and has quantitative methodology. The data used to identify the maturity levels were collected through questionnaires based on studies conducted by Ribeiro Junior (2016). The financial data were elaborated based on the PEARLS model, suggested by Santos (2016), both processed with the help of Stata and SPSS software. The sample was characterized as non-probabilistic, for convenience and intentional, and comprises 32 rural credit cooperatives located in the state of Paraná, belonging to credit cooperatives Cresol, active in Central Bank databases until December 2017. The method of analysis was based on multiple regression analysis. The main results pointed out that these cooperatives have the lowest levels of maturity within the Representativeness Guideline. This guideline represents practices related to assemblies processes, of account rendering to associates and electoral lawsuits. Within the Framework Directive are practices directed at the structures of administrative, fiscal and executive councils, the results demonstrated an initial level of maturity suggesting that there is much to be improved. The Guideline that stood out in this work was the Supervision, the results demonstrated the existence of practices that overcome the rules required by regulatory bodies. Regarding the objective of identifying if the corporate governance devices implemented influence the financial performance of rural credit cooperatives, the results allow to affirm that 37.5% of the financial operations of these cooperatives are influenced by devices of corporate governance, that is, of the 32 indicators described in the PEARLS model analyzed through the regression, 12 are influenced by the adoption of corporate governance practices.